2015
DOI: 10.2993/0278-0771-35.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Adapting in the Shadow of Annapurna: A Climate Tipping Point

Abstract: Rapid climate change in the Himalaya threatens the traditional livelihoods of remote mountain communities, challenges traditional systems of knowledge, and stresses existing socio-ecological systems. Through semi-structured interviews, participatory photography, and repeat photography focused on climate change and its impacts on traditional livelihoods, we aim to shed light on some of the socio-cultural implications of climate related change in Manang, a remote village in the Annapurna Conservation Area of Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…This observation is in line with other studies undertaken in similar altitudinal regions within the country: Kanchanjunga ), Khumbu (McDowell et al 2013 and Namche region (Smadja et al 2015) of eastern Nepal; and Mustang region (Manandhar et al 2011) and Manang region (Konchar et al 2015) of central Nepal.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This observation is in line with other studies undertaken in similar altitudinal regions within the country: Kanchanjunga ), Khumbu (McDowell et al 2013 and Namche region (Smadja et al 2015) of eastern Nepal; and Mustang region (Manandhar et al 2011) and Manang region (Konchar et al 2015) of central Nepal.…”
Section: Discussionsupporting
confidence: 93%
“…This is obvious as some studies (Chaulagain 2009;Shrestha & Aryal 2011) already reported low snowfall and rapid meltdown processes all over Nepal. Konchar et al (2015) reported less amount and irregular timing of snowfall in the Manang region of central Nepal. Because of this, local people mentioned that permanent snow line and snow cover thickness was reduced on the nearby mountain peaks such as Chanyanath, Rinimokshya and Chuchemara in Rara, and Langtang and Ganesh in Langtang.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Global factors cannot be mitigated locally but improved management practices that aid local conservation and development in this high mountain ecosystem are required (Garrard et al 2016). At lower altitudes within large ranges, a shift from traditional practices to a more diversified blend of agropastoralism, tourism services, and cash-crop production may become adaptive for local economies (Konchar et al 2015). Conservation must find its place within this changing dynamics.…”
Section: Tourism and Sport Pressuresmentioning
confidence: 99%